DAMPAK NEGATIF DAN POSITIF PENGGUNAAN MEDIA SOSIAL TERHADAP KINERJA KARYAWAN MILENIAL - Akbar, Adhadian (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to expand the literature on the impact of social media use on organizations, particularly among millennials, by proposing a model and validating the positive and negative impacts of social media on millennial work performance. The study also examined the role of narcissistic personality (as a characteristic of some millennial employees) in social media use in the workplace. This study used an online survey to collect data from millennial employees in Indonesia. The analysis used partial least squares structural equation (PLS-SEM) models and IBM® SPSS and SmartPLS software. Results from the analysis showed (1) significant indirect positive relationships between social media and work performance through social capital (i.e., network ties, shared vision, and trust) and knowledge transfer; (2) There is a significant relationship between millennial narcissistic personality and workplace social media use. The results also suggested that social media has an association with negative impacts, such as work pressure and burnout, meaning social media use will make users feel pressured about work and hold back energy due to burnout. However, there is no evidence that this negative impact has a significant effect on millennial work performance.